Strategi Promosi Kesehatan di Komunitas Terhadap Stigma Penderita HIV/ AIDS/ AIDS : Sistematik Review - Dina Putri Yulianti; Ella Nurlaella Hadi (Universitas Pahlawan Tuanku Tambusai, 2025)
HIV/AIDS is a significant global health challenge, both medically and socially. Stigma and discrimination against People Living with HIV/AIDS (PLWHA) are major barriers in addressing this issue, hindering access to healthcare and worsening the quality of life of PLWHA. This study aims to evaluate community-based health promotion strategies in reducing HIV/AIDS-related stigma. The research employs a systematic literature review method based on PRISMA guidelines, analyzing 28 relevant articles from Scopus, PubMed, and ProQuest databases. The results indicate that community-based public education, healthcare worker training, and social support play crucial roles in reducing stigma against PLWHA. Public education involving community and religious leaders is effective in improving understanding and reducing discrimination. Providing training for healthcare workers enhances their capacity to deliver non-discriminatory care. Social support from family, friends, and communities positively impacts the well-being of PLWHA. With this holistic approach, an inclusive and supportive environment for PLWHA is expected to be created. Keywords: HIV/AIDS, stigma, health promotion, social support, public education